Evaluating an on-line cleaning agent for mitigating organic fouling in a reverse osmosis membrane. (July 2021) - Park, Sanghun; Hong, Seok Min; Park, Jongkwan; You, Sunam; Lee, Younggeun; Kim, Eunggil; Cho, Kyung Hwa
Abstract: Cleaning-in-place (CIP) is a representative fouling management process from which the filtration performances of fouled membranes can be recovered. However, CIP can cause significant inefficiency in water production because frequent system restabilization is necessary for cleaning processes. This study applied a newly developed on-line cleaning agent (OCA, a feed water additive for fouling mitigation), to reduce the number of CIP by enhancing water productivity. Reverse osmosis filtration was performed to evaluate the effect of on-line cleaning on the mitigation of organic fouling originating from humic acid (HA) and bovine serum albumin. OCA increased the permeate flux in proportion to OCA concentration. In particular, OCA effectively reduced the fouling layer thickness by 22% when fouling was influenced by HA–Ca 2+ complexation, increasing water production by 5%. It also had a minor influence on bovine serum albumin fouling, producing a 1.4% increase in permeate flux. Furthermore, the pore blockage-cake filtration model was used to evaluate OCA cleaning performance through the reduction in fouling layer resistance and the growth parameter. The results demonstrated the advantages of OCA utilization for mitigating cake layer development. These findings imply that OCA can be an effective cleaning additive, especially in seawater and groundwater treatment processes with a high proportion of HA and calcium ions. Graphical abstract: Image 1 Highlights: OCA was applied to mitigate HA and BSA fouling in the RO process. OCA improved the water productivity of the RO membrane. OCA can effectively alleviate the fouling originating from HA–Ca 2+ complexation. The fouling mitigation performance of OCA was investigated by OCT and cold FE-SEM.